Alternating pH landscapes shape epithelial cancer initiation and progression: Focus on pancreatic cancer. (25th April 2017) - Pedersen, Stine F.; Novak, Ivana; Alves, Frauke; Schwab, Albrecht; Pardo, Luis A.
Abstract : We present here the hypothesis that the unique microenvironmental pH landscape of acid‐base transporting epithelia is an important factor in development of epithelial cancers, by rendering the epithelial and stromal cells pre‐adapted to the heterogeneous extracellular pH (pHe ) in the tumor microenvironment. Cells residing in organs with net acid‐base transporting epithelia such as the pancreatic ductal and gastric epithelia are exposed to very different, temporally highly variable pHe values apically and basolaterally. This translates into spatially and temporally non‐uniform intracellular pH (pHi ) patterns. Disturbed pHe ‐ and pHi ‐homeostasis contributes to essentially all hallmarks of cancer. Our hypothesis, that the physiological pHe microenvironment in acid‐base secreting epithelia shapes cancers arising in these tissues, can be tested using novel imaging tools. The acidic tumor pHe in turn might be exploited therapeutically. Pancreatic cancers are used as our prime example, but we propose that this concept is also relevant for other cancers of acid‐base transporting epithelia. Abstract : Cells in organs performing net acid‐base transport, like the pancreatic ductal and gastric epithelia, survive in an extraordinarily large and variable extracellular pH gradient. This renders epithelial and stromal cells pre‐adapted to the heterogeneous extracellular pH in the tumor microenvironment and may thereby contribute to the development of epithelial cancers.